Socialization of Law Number 2 of 1981 and Law Number 8 of 1999 to Make it Happen Orderly Measuring Trade Through Tera and Retracting Measurement Tools and Education of Traders in Berastagi Market and Students of SMA Negeri 2 Kabanjahe - Ginting, Junedi; Gustanto (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Sustainable Development Goals (SDGs) is a global action plan agreed upon by world leaders, including Indonesia, to end poverty, reduce poverty and protect the environment. SDGs contain 17 goals and 169 targets which are expected to be achieved by 2030. Universities are expected to help the government in strengthening SDGs programs. One of the 9th SDGs programs is "Building resilient infrastructure, increasing inclusive and sustainable industry, and encouraging innovation. In line with the 9th SDGs program, the people of North Sumatra Province who are highly dependent on agricultural livelihoods need innovation and empowerment programs to increase their efficiency and productivity. The Karo Regency area in North Sumatra Province has been developed into production centers for agricultural products such as vegetables and fruit. Berastagi is a fruit and vegetable producing center as well as a tourist area. As a producer and tourism center, the government has designated the Berastagi fruit market as an orderly market. However, it was found that the weighing measuring instruments owned by traders at the Berastagi fruit market did not have a valid stamp and had expired stamps, which resulted in a decrease in regional levy income for Karo Regency. Apart from that, the transfer of the D3 Metrology and Instrumentation study program in 2022 from FMIPA to USU's Faculty of Vocational Studies is not yet well known to the public, resulting in a decline in student interest in entering the D3 Metrology and Instrumentation study program, which has been proven to be far below the quota accepted in the 2023 new student admission achievement pathway. For this reason, through the community service program in 2023, it is necessary to introduce the D3 Metrology and Instrumentation study program through socialization activities on Law Number 2 of 1981 concerning Re-Terra and Re-Terra and Law Number 8 of 1999 concerning Consumer Protection, education on Re-Terra of Measuring Instruments. Weigh measuring instruments and carrying out re-testing of weighing measuring instruments for students and teachers at SMA Negeri 2 Kabanjahe and re-calibrating measuring measuring instruments owned by traders at the Berastagi fruit market and it is hoped that students and teachers at SMA Negeri 2 Kabanjahe will become informants about the importance of measuring instruments. repeat weighing measurements and have an interest in becoming a translatorthrough studying at the D3 Metrology and Instrumentation study program, USU Vocational Faculty.